Palestinian doctors’ views on patient-centered care in hospitals - Wasim I M Sultan; Mutaz I M Sultan; José Crispim (BMC Health Services Research, 2018)
Abstract Background Understanding the perceived importance of Patient-Centered Care (PCC) among Palestinian doctors and how the provider and other clinical characteristics may impact their views on PCC is essential to determine the extent to which PCC can be implemented. This study investigates the provision of PCC among hospital doctors in a developing and unstable country, namely, Palestine. Methods This descriptive, cross-sectional research employed self-report survey among 369 Palestinian doctors working in hospitals in 2016. Respondents completed the Provider-Patient Relationship Questionnaire (PPRQ) and were asked to rate the importance of 16 PCC subjects in a context-free manner. Then they scored the existence of eight contextual attributes in their workplace. Results Although 71.4% of the participants got training in communication, only 45% of the participants knew about PCC. 48.8% of doctors considered the “exchange of information” with patients most important PCC component. Clustering identified three groups of doctors: 32.4% of doctors reported good perceptions of PCC, 47.5% moderate; and 20.1% poor. Older, married, and specialist doctors and those familiar with PCC are more likely classified in the “good” cluster. Results revealed a significant difference between doctors’ views based on their gender, experience, marital status, previous knowledge about PCC, and type of hospital in favor of males, experienced, married, familiar with PCC, and doctors in private hospital respectively. The level of job interest, nurses’ cooperation, the tendency of patients to hide information, and doctor’s friendly style were positively related with more perceived importance of PCC. Conclusion We identified benchmark doctors who perceive the high relative importance of PCC. Our results highlighted knowledge gaps and training weaknesses among doctors in public and private hospitals in respect to their views on PCC. Decision makers may invest in the determined contextual predictors to enhance attitudes towards PCC. This work doesn’t address patients’ views on PCC.